1985
DOI: 10.1073/pnas.82.7.2148
|View full text |Cite
|
Sign up to set email alerts
|

In vivo solvent-suppressed localized hydrogen nuclear magnetic resonance spectroscopy: a window to metabolism?

Abstract: Solvent-suppression NMR techniques are combined with a pulsed magnetic field gradient and surface coil detection method of spatial localization. The result is a technique that enables observation of metabolites in the hydrogen (1H) NMR chemical-shift spectra from preselected disk-shaped volumes of biological tissue in vivo. Localized spectra are recorded from the normal human brain and forearm and from a dog in acquisition periods of 2 s using a 1.5-T imaging/spectroscopy system. This is several hundredfold fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(25 citation statements)
references
References 28 publications
0
25
0
Order By: Relevance
“…[203][204][205][206][207][208][209] Using these techniques, signal-to-noise ratio enhancements of more than 10,000:1 have been achieved in vitro. Historically, many metabolic pathways have been probed using either 14 C or (more recently) 11 C as radiolabels. It has also been shown that 13 C MRS studies using enriched 13 C have enormous potential for probing metabolic pathways.…”
Section: Summary and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…[203][204][205][206][207][208][209] Using these techniques, signal-to-noise ratio enhancements of more than 10,000:1 have been achieved in vitro. Historically, many metabolic pathways have been probed using either 14 C or (more recently) 11 C as radiolabels. It has also been shown that 13 C MRS studies using enriched 13 C have enormous potential for probing metabolic pathways.…”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…In 1985, Bottomley et al 14 published the first human in vivo solvent-suppressed proton spectrum of the brain (FIG. 2).…”
Section: Introductionmentioning
confidence: 99%
“…The recent development of human-sized magnets with fields up to 2.1 T along with techniques for obtaining spectra from localized volumes has made it possible to obtain 'H NMR brain spectra from humans (5,6). While human brain spectra have been obtained with coils surrounding the entire head (6), their sensitivity and spectral resolution have been low compared to animal studies.…”
mentioning
confidence: 99%
“…Recent advances in in vivo NMR have emphasized 31P and 1H and not '3C (6,7). However, the '3C studies of rats at 8.5 T (8,9) and rabbit at 1.9 T (10) indicated that the '3C NMR technique can reveal hepatic glycogen signals in vivo.…”
mentioning
confidence: 99%